Analysis of Farmer's Satisfaction Level with the Cattle and Buffalo Business Insurance Program (Auts/K) in Kahu Sub-District, Bone District - Besse Rizky Fortuna; Hastang Hastang; dan Aslina Asnawi (Journal of Global Innovations in Agricultural Sciences)
The Cattle and Buffalo Business Insurance Program (AUTS/K) is one of the programs provided by the government to farmers to provide protection from the risk of loss faced in the livestock business. This study aims to determine the level of farmer satisfaction and the efforts that can be made to improve farmer satisfaction with the AUTS/K program. This research was conducted from November 2022-January 2023 in Kahu District, Bone Regency. The population of this study is 34 farmers who participated in the AUTS/K program. Data collection methods began with observation and interviews using a questionnaire. The data analysis used is Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). Research variables include the dimensions of registration, implementation, claims, and stakeholders. The results show that the farmer's satisfaction level with the AUTS/K program is highly satisfactory (82.52%). Variables that are prioritized for improvement according to the IPA Cartesian diagram, namely the attributes of ease of claim submission procedures, timeliness of claim approval, timeliness of claim disbursement, and provision of socialization by field extension officers from the livestock service office. Efforts that can be made to improve the performance of these attributes are improving and simplifying the insurance claim process, increasing the quantity and quality of field extension officers and insurance officers, and increasing socialization activities. Keywords: Beef cattle, cattle and buffalo business insurance program, farmers, satisfaction.